Omental Infarction: Challenges in Managing Acute Abdomen During COVID-19 Pandemic - Asyraf Mohd Zuki; Wei, Woon Teng; Mah, Jin-Jiun; Muhammad Nur Syamim Che Johan; Aung Mra; Mohd Firdaus Mohd Hayati (Gazi Universitesi, 2022)
Acute abdomen is a common surgical emergency, yet is challenging especially during the COVID-19 pandemic. This article highlights the challenging management of acute abdomen and issues on preoperative nasopharyngeal swab testing, aerosol-generating procedures and non-operative management. A 36-year-old gentleman presented with acute right iliac fossa pain which was diagnosed as simple acute appendicitis and was managed non-operatively. He progressed well initially, but after 2 days, he developed localized abdominal guarding. The diagnosis was revised to perforated appendicitis and he was pushed to the operation theatre on the same day. Since the swab test was negative, we performed the surgery as a non-COVID-19 patient. To our surprise, the intraoperative finding was consistent with spontaneous omental infarction and mild appendicitis. Appendicectomy with omentectomy was done and the final diagnosis was consistent with acute omental infarction. Performing surgery on patients with active COVID-19 infection can lead to a high pulmonary complication and mortality rate. All cases require COVID-19 status as the screening prerequisites prior to admission and surgical intervention. Emergency cases such as acute abdomen warrant a surgical intervention regardless of COVID-19 status but with full personal protective equipment. Managing acute abdomen is challenging during the COVID-19 pandemic. The direction is towards non-operative management unless it is contraindicated. Omental infarction must be considered as one of the differential diagnoses for any patient with unexplained acute abdominal pain which warrants imaging assessment.